ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN: STUDI KASUS PADA GERAI INDOSAT SOLOBARU - Bunga Aisyah; Atik Lusia (Globalwriting Academica Consulting & Publishing, 2022)
The purpose of this study is to determine the impact of product quality, service quality, and customer trust on customer loyalty. Independent variables, consisting of product quality variables, service quality variables, and customer confidence variables, affect customer loyalty as dependent variables. This research was conducted at Indosat Sorovar Outlet. The data collection method in this study is a questionnaire completed by respondents, i.e. consumers of Indosat Solobaru outlets. His sample of 100 respondents to this survey using targeted sampling methods. The independent variables in this study consisted of product quality, service quality, and brand image, and the dependent variable was customer loyalty. The results of the analysis using multiple linear regression show that the variable product quality has a positive impact on customer loyalty. Second, fluctuating service quality has a positive effect on customer loyalty. Third, brand image has a positive effect on customer loyalty. The t-test analysis results show that product quality, service quality, and brand image have a significant impact on customer loyalty. Analysis using the coefficient of determination showed that 52.0% of the consumer loyalty variables could be explained by variations in product quality, service quality and brand image variables, and 48.0% could be explained by other variables not included in this study. shown.